gga-miR-200b-3p Promotes Macrophage Activation and Differentiation via Targeting Monocyte to Macrophage Differentiation-Associated in HD11 Cells - Lin, Wencheng; Zhou, Lianghui; Liu, Manqing; Zhang, Danmeng; Yan, Yiming; Chang, Yung-Fu; Zhang, Xiquan; Xie, Qingmei; Luo, Qingbin (Frontiers in Immunology, 2020)
MicroRNAs (miRNAs) play a critical role in various biological processes through regulating gene expression post-transcriptionally through degradation of mRNAs or inhibition of translation by binding to complementary sites primarily in the 3′UTRs of mRNAs. Although miRNAs are involved in cell proliferation and differentiation in mammals, few reports are available regarding the effects of host miRNAs on macrophage activation and differentiation in birds. Here, we reported that gga-miR-200b-3p acts as a positive regulator enhancing macrophage activation and differentiation. We found that ectopic expression of gga-miR-200b-3p in HD11 cells enhances the amount of MHC-II-positive cells and promotes the expression of pro-inflammatory cytokines, that gga-miR-200b-3p directly targets monocyte to macrophage differentiation-associated (MMD), and that inhibition of MMD by gga-miR-200b-3p enhances the activation and differentiation of HD11 cells and increases the expression of pro-inflammatory cytokines. Collectively, these findings highlight a crucial role of gga-miR-200b-3p in macrophage activation and differentiation in birds.